The more the merrier: recent hybridization and polyploidy in cardamine - Mandáková, Terezie; Kovarík, Ales; Zozomová-Lihová, Judita; Shimizu-Inatsugi, Rie; Shimizu, Kentaro K; Mummenhoff, Klaus; Marhold, Karol; Lysak, Martin A (The Plant cell, 2013)
This article describes the use of cytogenomic and molecular approaches to explore the origin and evolution of Cardamine schulzii, a textbook example of a recent allopolyploid, in its ~110-year history of human-induced hybridization and allopolyploidy in the Swiss Alps. Triploids are typically viewed as bridges between diploids and tetraploids but rarely as parental genomes of high-level hybrids and polyploids. The genome of the triploid semifertile hybrid Cardamine × insueta (2n = 24, RRA) was shown to combine the parental genomes of two diploid (2n = 2x = 16) species, Cardamine amara (AA) and Cardamine rivularis (RR). These parental genomes have remained structurally stable within the triploid genome over the >100 years since its origin. Furthermore, we provide compelling evidence that the alleged recent polyploid C. schulzii is not an autohexaploid derivative of C. × insueta. Instead, at least two hybridization events involving C. × insueta and the hypotetraploid Cardamine pratensis (PPPP, 2n = 4x-2 = 30) have resulted in the origin of the trigenomic hypopentaploid (2n = 5x-2 = 38, PPRRA) and hypohexaploid (2n = 6x-2 = 46, PPPPRA). These data show that the semifertile triploid hybrid can promote a merger of three different genomes and demonstrate how important it is to reexamine the routinely repeated textbook examples using modern techniques.
Keywords: Cardamine; sekvence nukleotidů; Triploidy; druhová specificita; Phylogeny; Hybridization, Genetic; In Situ Hybridization; Sequence Analysis, DNA; hybridizace in situ; Molecular Sequence Data; molekulární sekvence - údaje; Biological Evolution; genová dávka; hybridizace genetická; nestabilita genomu; triploidie; Genome, Plant; sekvenční analýza DNA; Base Sequence; fylogeneze; biologická evoluce; Species Specificity; Genomic Instability; polyploidie; Polyploidy; genom rostlinný; Gene Dosage